Anticancer Potential Of Dillenia Bracteata: Evaluation Of Methanol Extract And Its Isolated Compound In Ehrlich Ascites Carcinoma-Induced Swiss Albino Mice - Kota, Sandhya; Raj R, Senthil (Journal of Neonatal Surgery, 2025)
Background: Cancer poses a significant health issue worldwide even though chemotherapy treatment creates major side effects in patients. Scientists find interest in the cancer prevention value of Dillenia bracteata Wight through herbal medicine research. This research analyzes the antitumor effects of Dillenia bracteata when given to Swiss albino mice with Ehrlich Ascites Carcinoma. Objective: This research studied how MEDB and IF-D affect tumor growth in mice with EAC carcinoma and their effects on blood health and cell life along with liver function and inflammation markers. Methods: Methanol extract was prepared from the dried leaves of Dillenia bracteata (MEDB) and active principle compound (IF-D) were isolated through column chromatography. Our research investigated MEDB and IF-D doses that were safe in the mice and then grouped them for investigation of invivo activity in EAC induced carcinoma. Researchers evaluated tumor size, weight, survival length, cell viability and essential blood chemistry results for all mice included in the study. Our research examined inflammatory markers like IL-6 and TNF along with hepatic condition tests and antioxidants SOD, GSH, CAT, MDA, plus total protein and enzyme measurements. Results: Both MEDB and IF-D treatment brought about significant tumor size reduction and weight loss while making EAC-induced mice live longer. The isolated compound IF-D treated cancer cells better than MEDB and standard drug 5-fluorouracil (5-FU) activity. The treatment with IF-D therapy reduced tumor living cells while improving blood parameters and PCV. IF-D demonstrated great anti-inflammatory properties when it lowered IL-6 and TNF-α activity and strengthened natural defenses against oxidative damage. Hepatic parameters recovered completely because IF-D restored regular SGPT SGOT and ALP test results. Conclusion: Results showed that the compound IF-D from Dillenia bracteata reduced cancer cells effectively while maintaining safe properties to study further its use in treating cancer patients. Research studies should test the plant extract IF-D because it shows great promise to control cancer development and protect liver health